Understanding the mechanical behaviour of 718 and 625 + nickel based super-alloys under cathodic polarization. (April 2021) - Martelo, D.F.; Morana, R.; Akid, R.
Highlights: Nitrides and Carbides present in the matrix do not appear to be preferential sites for hydrogen induced cracking. Mo and Cr carbides at the grain boundaries of alloy 625+ may explain is a possible explanation for the increased susceptibility to HE of AR 625+ over that of AR 718. Increased grain size causes an increase in HE susceptibility, however, such effects are negligible compared to the effect oflarge precipitation of δ phase or carbides at grain boundary. Abstract: The effect of hydrogen on the mechanical behaviour of UNS N07718 (alloy 718) and UNS N07716 (alloy 625 + ) nickel based super-alloys was studied. Atomic hydrogen was introduced into the metal during Slow Strain Rate Tests (SSRTs) via an electrochemical technique, following the method described in [1], this is a standard used in the oil and gas industry to assess the performance of precipitation hardened nickel based alloys towards hydrogen embrittlement (HE). Different heat treatment conditions, used to produce different microstructures, were selected to highlight the effect of specific microstructural phases/ features on the HE susceptibility, including: a Solution Annealed (SA) microstructure, a microstructure with a high volume fraction of delta phase (δ), a microstructure containing low volume fraction of gamma prime (γ') and gamma double-prime (γ''), the As Received material (AR) and a Coarse Grain Size (CGZ) microstructure. For each microstructural condition, the mechanical performance under electrochemical hydrogenating conditions was compared against that obtained in an inert (glycerol) environment to evaluate and quantify the susceptibility to HE. In addition, an analysis of fracture surfaces was carried out to assess the preferential mode of fracture. Results revealed that in low magnification images the Hydrogen charged samples showed smooth featureless areas on the fracture surface. HE susceptibility was seen to increase as the volume fraction of the precipitates increased whilst grain size had negligible effect. 625 + displayed higher susceptibility to HE compared to 718.